Antagonism of Indigenous Fungi Collected from the Bamboo Clump against Fusarium sp., the Cause of Fusarium Wilt Disease in Garlic: Daya Antagonis Jamur Indigenus dari Rumpun Bambu terhadap Fusarium sp., Penyebab Layu Fusarium pada Bawang Putih - Lestiyani, Ayu; Fauziah, Lia; Sugiyarto, Sugiyarto (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2022)
Indigenous fungi can be found around bamboo clumps. This study aimed to identify indigenous fungi isolated from the bamboo clump as biological control agents against pathogenic fungi of Fusarium sp. in garlic. The study was conducted from June to September 2021 at the Laboratory of Pest and Disease Observation, Temanggung Regency, Central Java, Indonesia. The current research design involved the following three steps, (1) Isolation and identification of the pathogenic fungi of Fusarium sp. in garlic, (2) Isolation and identification of indigenous fungi collected from the bamboo clump, and (3) Antagonism test of indigenous fungi isolated from the bamboo clump against Fusarium sp. in-vitro. The results showed that ten species were successfully identified, and five species had the potential as biological control agents against Fusarium sp. in garlic; Penicillium sp., Mucor sp., Aspergillus sp1, Aspergillus sp2, and Tricho-derma sp. Trichoderma sp. revealed the highest antagonism (66.71%), while Penicillium sp. revealed the lowest antagonism (32.925%) against Fusarium sp. Based on their antagonistic potential, Trichoderma sp. showed the highest ability to suppress Fusarium sp. (66.71%), while the lowest one was Penicillium sp. (32.92%).